An Econometric Study of Net FDI Inflows Across BRICS Economies: Trends, Determinants, and Policy Implications - Deepak Kumar, Renu Verma, Subhash, Bharti (Journal of Neonatal Surgery, 2025)
This paper addresses the factors that drive Foreign Direct Investment (FDI) inflows in a sample of other BRICS economies (Brazil, Russia, India, China and South Africa) from 2008 to 2023 with special attention to such variables as: GDP, capital formation, economic growth and inflation. Based on time series data from WDI and UNCTAD, the paper uses regression analysis to assess the impact of political risk, trade openness, inflation, stability, and labour on FDI stocks and flows. The results are expected to show a positive and significant impact on FDI for large GDP size and gross capital formation, as they indicate a good potential for the market and infrastructure. Higher economic growth is expected to influence FDI positively, adding to the high-growth appeal of the BRICS! Inflation will have a subtler role—some inflation is good in that it reveals demand is increasing, but too much price predictability can drive away long-term investment. The findings of the paper should especially interest policymakers who want to improve FDI inflows. Smaller-GDP economies like those in South Africa may thrive with more sectoral and targeted incentives to offset their lack of size in this regard. Capital formation via infrastructural development is highlighted as a central approach towards attracting efficiency-seeking FDI in this regard. Continued macroeconomic stability — a combination of growth and low inflation — is also vital for sustaining investor confidence. It can also identify different determinants of FDI across the BRICS and this may imply that the same policy context may not work the same within the BRICS. Furthermore, by exploring these determinants, the research highlights tangible insights on how to optimize investment promotion strategy in emerging markets, in the context of a global economy that is witnessing quick changes in FDI patterns following the pandemic. This study has implications for both theory and policy related to FDI in dynamic emerging economies.